El depositario judicial en los delitos de apropiación ilícita y peculado por extensión. Comentario al precedente vinculante de la Corte Suprema de la República - Oré Sosa, Eduardo (2020)
The Supreme Enforceable foresees a conflict of laws among articles 190 and 392 of the Penal code, since both make reference to appropriation in status of trustee. The resolution establishes that the most favorable norm should be applied; in this case the offense of unlawful appropriation. The author considers that regardless of the similarity between these dispositions, they have not been equally valued by the legislator. He states that when the execution of the behavior by the trustee assigned by the competent authority, implies an aggression to a patrimonial interests of the Administration, we will be facing an offense against the Public Administration. And it is framed as an unlawful appropriation in its aggravated form, when a judicial trustee is only charged with affecting patrimony of an individual.